Exploring the Linkage Between Commodity Chain Profile and Performance: A Case Study of Sawn Wood in Uganda - Kyeyune Kambugu, Robert; Abwoli, Yabezi Banana; Okure, Mackay (The Open Forest Science Journal, 2013)
Secure supply of wood remains a challenge partly due to resource conservation efforts that have failed to focus on the sawn wood supply chain as a whole. This study investigated the influence of sawn wood commodity chain profile on its performance. Data were collected from the production and distribution chain of 35 production units selected randomly. Production batches comprising of at least fifteen logs each were used at each unit to collect data on volume recovery factor, value addition and revenue distribution between participants in the unit’s distribution chain. One-way multivariate analysis of variance was used to test the hypothesis that there is no difference in performance parameters between the sawn wood commodity chain channels. Results revealed a significant multivariate effect (p<0.05) for channel of operation on performance thus rejecting the null hypothesis. Univariate ANOVA showed significant difference (p<0.05) between the channels on all the three performance parameters. It was recommended that factors influencing the performance parameters be investigated and standards established for benchmarking; the three performance dimensions be integrated into a single index for assessing the overall performance; and the impact of sawn wood commodity chain performance on sawn wood supply sustainability be investigated.
Keywords: Distribution equity; Efficiency; Sustainability; Timber commodity chain; Value addition